Peripheral Venous Catheter-Related Adverse Events: Evaluation from a Multicentre Epidemiological Study in France (the CATHEVAL Project) - Miliani, Katiuska (PLoS One, 2017)
INTRODUCTION: Peripheral venous catheters (PVC) are medical devices most frequently used during hospital care. Although the frequency of specific PVC-related adverse events (PVCAEs) has been reported, the global risk related to the insertion of this device is poorly estimated. The aim of this study is to determine the incidence of PVCAEs during the indwell time, after catheter removal, and to identify practice-mirroring risk factors. METHODS: A prospective observational study was conducted as a part of a research project, called CATHEVAL, in one surgery ward and four medicine wards from three public general tertiary care hospitals in Northern France that were invited to participate between June-2013 and June-2014. Each participating ward included during a two-month study period all patients older than 15 years carrying a PVC. All inserted PVCs were monitored from insertion of PVC to up to 48 hours after removal. Monitored data included several practice-mirroring items, as well as the occurrence of at least one PVCAE. A multivariate Cox proportional hazard model, based on a marginal risk approach, was used to identify factors associated with the occurrence of at least one PVCAE. RESULTS: Data were analysed for 815 PVCs (1964 PVC-days) in 573 patients. The incidence of PVCAE was 52.3/100 PVCs (21.9/100 PVC-days). PVCAEs were mainly clinical: phlebitis (20.1/100 PVCs), haematoma (17.7/100 PVCs) and liquid/blood escape (13.1/100 PVCs). Infections accounted for only 0.4/100 PVCs. The most frequent mechanical PVCAEs, was obstruction/occlusion of PVC (12.4/100 PVCs). The incidence of post-removal PVCAEs was 21.7/100 PVCs. Unstable PVC and unclean dressing were the two main risk factors. CONCLUSION: Limitation of breaches in healthcare quality including post-removal monitoring should be reinforced to prevent PVC-related adverse events in hospital settings.